The prevalence and spectrum of mucocutaneous disease in South African people living with HIV and accessing care at a district-level hospital - Saskya Claasens; Susanna M.H. Kannenberg; Henry F. Jordaan; Karis Moxley; Rhodine Smith; Johann de Wet; Willem I. Visser (AOSIS, 2020)
Background: Although the association between human immunodeficiency virus (HIV) and mucocutaneous diseases has been well studied within South African specialist centres, there is limited data from district-level hospitals. Available data may, therefore, fail to reflect the prevalence and full spectrum of dermatoses seen in people living with HIV (PLWH). Objectives: To determine the prevalence and spectrum of dermatoses seen in PLWH. Method: We conducted a cross-sectional, descriptive study of 970 PLWH (men and women, ≥ 18 years old) accessing care at Karl Bremer Hospital, a district-level hospital located in the Western Cape province, South Africa, between 01 September 2016 and 28 February 2017. Results: The prevalence of mucocutaneous disease in this sample was 12.7% (95% confidence interval [CI] 0.11-0.15). Non-infectious dermatoses comprised 71.0% of the disorders. Pruritic papular eruption (20.0%) and seborrheic dermatitis (6.0%) were the most common non-infectious dermatoses. Tinea corporis (8.0%) and oral candidiasis (6.0%) were the most prevalent infectious dermatoses. There was no significant association between skin disease category (infectious or non-infectious dermatoses) and patient demographics (gender and ethnicity) or HIV-disease characteristics (CD4+ cell count, viral load and duration of antiretroviral therapy [ART]). Conclusion: This study provides valuable scientific data on the prevalence and spectrum of mucocutaneous disease in PLWH attending a South African district-level hospital. Prospective studies conducted in other district-level centres across the country are required to determine the lifetime prevalence and spectrum of dermatoses in PLWH in the ART era.